2017
DOI: 10.18857/jkpt.2017.29.2.62
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impacts of Stroke Patients Disease-Related Characteristics on Depression and Family Support.

Abstract: Purpose: This study was conducted to identify the impacts of stroke patients' general and disease-related properties on depression and family support. Methods: Subjects consisted of 79 persons who were diagnosed with cerebral hemorrhage and cerebral infarction and met the criteria for selection. The Korean version of Beck depression inventory (BDI) and a revision of the family support developed by Cobb were used. Frequency analysis of the subjects' general and medical history properties was conducted, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In obtaining the physical results from these models, the pole mass plays an important role in the process where the characteristic scale is close to the mass shell [2]. It was shown that the pole mass is infrared finite [3] and invariant under the renormalization group [4]. In case of the quantized gauge field theory, we need to add a gauge-fixing terms [5] which contain a gauge parameters and the physical quantities such as the pole mass should be independant of these gauge parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In obtaining the physical results from these models, the pole mass plays an important role in the process where the characteristic scale is close to the mass shell [2]. It was shown that the pole mass is infrared finite [3] and invariant under the renormalization group [4]. In case of the quantized gauge field theory, we need to add a gauge-fixing terms [5] which contain a gauge parameters and the physical quantities such as the pole mass should be independant of these gauge parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These beta functions take different forms when calculated in different renormalization schemes [5] and in most of the cases, they are obtained in the symmetric phase with the MS scheme [6] and the pole masses we are interested in are those in the broken symmetry phase. Hence, it seems to be necessary to investigate the renormalization group(RG) behavior of the physical quantities such as the pole mass in the broken phase under the beta functions in the symmetric phase and it was shown that if the pole mass was expressed in terms of the Lagrangian parameters in the symmetric phase it is RG invariant under the beta and gamma functions obtained in the symmetric phase in the minimal subtractions(MS) scheme in case of the neutral scalar and the Abelian Higgs model [7] [8] and also have shown the gauge parameter independence [9]. Recently, the models with non-minimal Higgs bosons are of interest in the new physics to solve the question of the origin of the neutrino mass, matter-antimatter asymmetry in the universe and the nature of dark matters [10] and in this paper, we will investigate the RG behavior of the Higgs pole mass in these multi-Higgs model by generalizing the method that we have used in [7] [8].…”
mentioning
confidence: 99%